2006
DOI: 10.1161/01.atv.0000193567.88685.f4
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Neutrophil Gelatinase–Associated Lipocalin in Atherosclerosis and Myocardial Infarction

Abstract: Objective-Neutrophil gelatinase-associated lipocalin (NGAL) modulates the activity of matrix metalloproteinase (MMP) 9, an important mediator of vascular remodeling and plaque instability in atherosclerosis. This study aimed to analyze the expression of NGAL in atherosclerotic plaques and myocardial infarction (MI). Methods and Results-Atherosclerotic apolipoprotein E (apoE)Ϫ/Ϫ ϫ low-density lipoprotein receptor (LDLR) Ϫ/Ϫ and C57BL/6J control mice were exposed to brief hypoxic stress (10 minutes of 10% oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
240
3
8

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(262 citation statements)
references
References 45 publications
(46 reference statements)
11
240
3
8
Order By: Relevance
“…It has been reported that hypoxic stress and acute infraction increase Lcn2 expression in mouse macrophages (Hemdahl et al 2006, Jiang et al 2008). This supports the idea that expression of lipocalin-2 is a response that these cells show against hypoxic stress.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that hypoxic stress and acute infraction increase Lcn2 expression in mouse macrophages (Hemdahl et al 2006, Jiang et al 2008). This supports the idea that expression of lipocalin-2 is a response that these cells show against hypoxic stress.…”
Section: Discussionmentioning
confidence: 99%
“…Work to date has focused principally on the proinflammatory and metabolic effects of Lcn2 (11,13,(51)(52)(53)), yet less is known regarding cardiovascular effects. Several studies have now shown that Lcn2 was elevated during ischemia-reperfusion processes and in coronary heart disease and myocardial infarction (12,20,21,23). Here, we analyzed the effect of Lcn2 on cardiomyocyte apoptosis, an important component of cardiac remodeling leading to heart failure (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that Lcn2 may mediate the innate immune responses in the pathogenesis of heart failure (17)(18)(19)(20). Lcn2 expression is significantly augmented in patients with coronary heart disease and myocardial infarction (12,21). Plasma Lcn2 was increased after carotid artery injury in rats (22) and in a heterotopic mouse transplanted heart after ischemia/ reperfusion (23).…”
mentioning
confidence: 99%
“…The formation of a complex with NGAL and MMP-9 is crucial for atherotic plaque erosion and thrombus formation (12)(13)(14). Hemdahl et al have shown increased expression of NGAL and co-localization with MMP-9 in atherosclerotic plaques and myocardial infarction lesions (15).…”
Section: Introductionmentioning
confidence: 99%